Efikasi Pemantauan Hemodinamik Non-Invasif Pada Pasien Gagal Jantung: Literature Review - Aan Nuraeni; Ristina Mirwanti; Firman Sugiharto; Dylla Istiazahra; Elsa Egawati Sonandar; Kintan Komala; Meisha Nurlianti Hidayat; N Nunik Virgianty; Neng Anisa Purnama Cahya; Sandra Restuti; Wahyu Pratiwi (Jurnal Keperawatan Muhammadiyah, 2022)
Objectives: Therefore, this literature review aimed to identify the efficacy of non-invasive monitoring to evaluate the hemodynamics of patients with HF. Methods: This study was a literature review. Keywords include “heart failure patients” AND “non-invasive hemodynamic monitoring” AND “invasive hemodynamic monitoring” and searched extensively through Springer Link, PubMed, and Science Direct. Data analysis was assisted by a data extraction table and qualitative analysis. Result: Seven articles were included in the qualitative analysis after being selected through the title, abstract, and inclusion-exclusion criteria. The analysis revealed that non-invasive hemodynamic monitoring in heart failure patients could be carried out in the Intensive Care Unit,  non-intensive care unit, and at home. The Non-invasive Pulse Contour Analysis (NPCA), caretaker BP device, and Photoplethysmography-Based Device were used in the ICU. While in the non-ICU, Ballistocardiography (BCG) and Impedance Cardiography (ICG) were used, and Non-Invasive Telemonitoring in bioimpedance monitoring can be used in the home setting.  Conclusions: Overall, the use of technology to monitor hemodynamics in heart failure patients non-invasively had good validation and efficacy compared with invasive monitoring. Furthermore, this non-invasive technology can be used in the ICU, in Non-ICU settings, and at home (telemonitoring).